Determination of thermal diffusivity of bulk corn kernel and bulk milled corn kernel using numerical method. Issue 1 (February 2021) - Waluyo, S; Ardiyanto, A; Telaumbanua, M
Abstract: Drying and storage of agricultural products are often related to heat transfer processes, both within the material and between the material and its environment. Thermal diffusivity is one of the thermo-physical properties related to the heat transfer processes in the material. This study aims to measure the thermal diffusivity of shelled corn, milled corn passed mesh 6, milled corn passed mesh 8, and milled corn passed mesh 16 (corn flour) fed by an axial heat source of 50 °C and 70 °C. The temperature sensors LM35 were used to gauge temperature history and were placed at 9 points in the test cylinder. The thermal diffusivity is then estimated from the temperature distribution data using numerical method. We found that the thermal diffusivity of shelled corn, milled corn passed mesh 6, milled corn passed mesh 8, and milled corn passed mesh 16 (corn flour) are (1.35, 1.38, 1, 69, and 2.30) x10 −7 m 2 /s, respectively, at axial heat source of 50 °C and (1.39, 1.42, 1.72, and 2.36) x10 −7 m 2 /s, respectively, at axial heat source of 70 °C. The smaller the bulk density and the larger the heat source provided, the higher the thermal diffusivity.